Research productivity and gender of research award recipients in international ophthalmology societies - Albert Y Wu; Anne Xuan-Lan Nguyen; Dipti Satvi Venkatesh; Ankita Biyani; Sanyam Ratan; Gun Min Youn (BMJ Open Ophthalmology)
Purpose The purpose of this study is to assess the research productivity and gender of award recipients of ophthalmology research awards in international societies.Methods This is a retrospective, observational study. The study population included award recipients of research awards from 36 ophthalmologic societies (listed on the International Council of Ophthalmology database) in 99 years (1922–2021). A gender-specific pronoun and a photograph of each award recipient were extracted from professional websites to assign their gender. Research productivity levels were retrieved from the Elsevier Scopus author database. The main outcome measures were gender distribution of award recipients per year, mean h-index per year, mean m-quotient per year, mean h-index by society, and mean m-quotient by society.Results Out of 2506 recipients for 122 awards, 1897 (75.7%) were men and 609 (24.3%) were women. The proportion of woman recipients increased from 0% in 1922 to 41.0% in 2021. Compared with 2000–2010 (19.8%, 109 of 550), women received a greater proportion of awards (48.4%, 459 of 949) in the last decade, from 2011 to 2021. Furthermore, men more often had greater h-index scores and m-quotient scores.Conclusions Women received awards (24.3%) at a lower rate than men (75.7%) while also exhibiting lower productivity, supporting the existence of a gender disparity. Our study found that women are under-represented in research awards, and further investigation into award selection processes and gender membership data is recommended.